Cyano and potassium-rich g-C3N4 hollow tubes for efficient visible-light-driven hydrogen evolution. Issue 13 (20th June 2019) - Yang, Jian; Liang, Yujun; Li, Kai; Yang, Gui; Wang, Kun; Xu, Rui; Xie, Xianjun
Abstract : Novel K + and cyano group decorated g-C3 N4 hollow tubes were constructed via a facile one-step molten salt assisted strategy. Abstract : Novel K + and cyano group decorated g-C3 N4 hollow tubes (T-CN) were designed and constructed via a facile molten salt route. Notably, the T-CN exhibited an excellent photocatalytic hydrogen evolution efficiency ascribed to the large surface area, efficient visible light absorption, and fast charge transfer and separation.